Influence of the new regulated device (OMEGA OSB12) on the kinematic variables of the competitive backstroke start - Qiu, X.; Correas, R.; Navarro, E.; Veiga, S. (World Congress of Performance Analysis of Sport XII, 2018)
Introduction: The latest version start device (OMEGA OSB12) was allowed to use in swimming races in order to avoid swimmers` feet slipping and to add tactile feedback during the backstroke start. However, the impact of such device on biomechanical variables or start performance are unknown. Therefore, the aim of this study was to analyse the influence of the new device on kinematic variables of the backstroke start. Methods: Ten national and international competitive level swimmers (16.0 ± 1.29 years. 56.4 ± 6.88kg, 1.67 ± 0.05m) completed three sprints of 25m at the maximum speed possible, using in each of them (in a random order) a start without start device, with start device in position -4 and 0. The aerial and subaquatic phases of the starts were recorded with the technique DLT-2D to acquire the real coordinates. The swimmer`s twenty-one body landmarks were manually digitized into key events of the start. Variables of temporal, spatial, velocity, angular, kinematic and the parameters of swim stage were calculated. The comparisons were undertaken among three start positions via the non-clinical magnitude-based inference. Results: The new device decreased the time in 5m (ES: 0.05 and 0.21) and increased the velocity in 10 and 15m (ES: -0.05 to -0.23). The time of hand release, take-off and entry, the initial height, release height, release distance, take-off height, entry height, entry distance, height of maximum depth and distance of maximum depth of swimmers using the device were increased (ES: -0.16 to -1.85) There were increases in velocity of release at Yaxis and entry at X axis (ES: -0.23 to -1.01): and decreases in take-off at X axis, entry at Y axis, complete immersion at X axis and maximum depth atX axis when using the device (ES: 0.38 to 0.55). The angle of release, entry and complete immersion increased (ES: -0.27 to -0.98) while the angle of take-off decreased (ES: 0.43 and 0.44) using the device. Discussion: The study showed that the following start-related variables: time of hand release to 5m. take-off and entry distances reached by center of mass (CM), velocities of CM in key positions, angles of hand release, entry, immersion and velocities in 5.10 and 15m. were improved after using new regulated device. The previous studies found that these variables are related to the performance of backstroke start. Thus, the new device helps to improve the performance of swimmers in backstroke start.